2015
DOI: 10.1002/bjs.9969
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of benefits of portal–superior mesenteric vein resection in pancreatic resection for ductal adenocarcinoma

Abstract: This meta-analysis showed increased postoperative mortality, higher rates of non-radical surgery and worse survival after pancreatic resection with PV-SMV resection. This may be related to more advanced disease in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(98 citation statements)
references
References 60 publications
3
87
2
3
Order By: Relevance
“…This difficulty in accurately selecting which patients should proceed with resection means that the a priori decision for NAT almost inevitably commits a patient with BR-PDAC to a trial dissection after NAT, providing distant metastases do not arise in the interim. This almost certainly results in an increased proportion of patients undergoing trial dissection and synchronous vein resection (36), and probably without a reduction in the R1/R2 rate (37). Whether it is possible to more accurately stage the margins of concern with endosonography and fine needle aspiration for cytology remains to be seen (38).…”
Section: Accurate Re-staging Of Br-pdac After Nat Is Not Possiblementioning
confidence: 99%
See 1 more Smart Citation
“…This difficulty in accurately selecting which patients should proceed with resection means that the a priori decision for NAT almost inevitably commits a patient with BR-PDAC to a trial dissection after NAT, providing distant metastases do not arise in the interim. This almost certainly results in an increased proportion of patients undergoing trial dissection and synchronous vein resection (36), and probably without a reduction in the R1/R2 rate (37). Whether it is possible to more accurately stage the margins of concern with endosonography and fine needle aspiration for cytology remains to be seen (38).…”
Section: Accurate Re-staging Of Br-pdac After Nat Is Not Possiblementioning
confidence: 99%
“…Over-reliance on a surgery-first approach for PDAC has retarded progress. The reality is that surgery and even more radical surgery, though well intentioned, has not yielded acceptable results (9,37). And while we can be pleased that there has been a significant decrease in pancreatoduodenectomy-related morbidity and mortality over the last 3 decades (5), the efficacy of surgical treatment has reached its ceiling (5).…”
Section: Accurate Re-staging Of Br-pdac After Nat Is Not Possiblementioning
confidence: 99%
“…However, more recent data have shown that a venous resection during pancreatic resections for PDAC is associated with increased rates of complications (41)(42)(43)(44). A posterior or a mesenteric approach appears to facilitate a venous resection and reconstruction during pancreatico-duodenectomies for PDAC (7,27,45,46).…”
Section: Borderline Resectable Pdacmentioning
confidence: 99%
“…A posterior or a mesenteric approach appears to facilitate a venous resection and reconstruction during pancreatico-duodenectomies for PDAC (7,27,45,46). Recent meta-analyses have shown that patients with venous resection during pancreatico-duodenectomies for PDAC have significantly lower negative resection margins and survival rates (41,43). The histological proof of venous invasion in PDAC has a detrimental effect on survival rates after pancreatectomies with venous resection for PDAC (42,47,48).…”
Section: Borderline Resectable Pdacmentioning
confidence: 99%
“…65 Only one recent large meta-analysis evaluating all types of pancreatectomy (PD, total pancreatectomy, and distal pancreatectomy) demonstrated that patients undergoing PV-SMV resection had increased mortality, higher rates of R1/R2 resections, and worse survival. 56 Numerous studies have found that tumor-free margins 14 46 For tumors located in the pancreatic neck involving the SMV, PV, and termination of the splenic vein, a procedure termed ''Whipple at the splenic artery'' (WATSA) has been described by Strasberg et al 69 for a series of 10 cases demonstrating no mortality. This approach requires isolation of the SMV below and the PV above the pancreas, followed by division of the splenic vein precisely where the splenic artery comes in contact with the pancreas superiorly.…”
Section: Venous Resectionmentioning
confidence: 99%